Pengaruh Perluasan Merek Terhadap Citra Merek (Studi Pada Frestea-Frestea Green) - Santoso, Radityo Kusumo; Grataridarga, Niko (Jurnal Vokasi Indonesia, 2018)
With the growing trend of the community regarding the need for a healthy minimum, encouraging beverage producers to answer this trend by issuing new products, which in the launch of new products in addition to introducing new products of the producers also at the same time want to create strong brand equity. Therefore, manufacturers use brand extensions. The purpose of this study is to analyze the effect of brand extension on brand image. This research is a quantitative approach research with explanatory analysis and multiple linear regression, the instrument that the researcher uses is a questionnaire. Based on the results of the study stated that one of the five dimensions, namely: perceived quality, significantly affects the brand image, while the other four dimensions do not significantly influence. The results of the analysis show that brand expansion affects the brand image by 59.7%, while the remaining 40.3% is influenced by other variables.